Experimental Investigation for a Novel Prototype of a Thermoelectric Power Generator With Heat Pipes - Liu, Yan; Shi, Zhaochun; Wang, Guohua; Yan, YuYing; Zhang, Yingchao (Frontiers in Energy Research, 2021)
In order to obtain the power generation of the thermoelectric power generator (TEG) group, a similar structure of the disc sandwich structure and an experimental system are built to analyze the power generation performance and temperature characteristics. To improve heat transfer and move heat from the hot side to the cold side, heat pipes with high thermal conductivity are arranged on the adjacent cold and hot plates of the TEG. The similar sandwich structure has 17 cold plates and 17 hot plates for the TEG pieces, which are connected in series on the circuit. Working conditions are hot air flow and cold water flow; hot air temperature and cold water temperature are set to a fixed temperature. The power generation of a single TEG is tested for verifying linear changes in the power generation performance with temperature differences (Td). Experimental results are that the power generation is improved by the air flow and water flow increasing. The water flow has a smaller effect on the power generation than the air flow. In the cold side of TEG pieces, the temperature of the cold side showed a gradual upward trend, the temperature of the hot side showed a wave trough phenomenon, and the Td showed a wave trough phenomenon. The hot air flow and the cold water changing cannot weaken the temperature trend of the hot side and the cold side. The hot air flow can more significantly increase the Td than the cold water.